The Role of Parental Depression on Adolescent Depression in Indonesia - Rofingatul Mubasyiroh; Indri Yunita Suryaputri; Alifa Syamantha Putri; Diana Setiyawati; Irmansyah; Suparmi; Ning Sulistiyowati; Doni Lasut; Oktarina (Wolters Kluwer Medknow Publications, 2024)
Introduction: Depression is one form of common mental disorder that significantly impacts adolescents. The emotional well-being of parents and family can directly influence adolescents' mental states. This study aimed to assess the association between parental depression and adolescents aged 15-19 years. Methods: This study utilized data from the third, fourth, and fifth cycles of the Indonesian Family Life Survey (IFLS) conducted jointly by Research and Development Corporation and Universitas Gadjah Mada. Adolescent depression was assessed using the Center for Epidemiologic Studies Depression-10, in which IFLS-5 (2014) data were analyzed. At the same time, parental depression was measured using data from IFLS-4 (2007) and IFLS-5 (2014). The study sample consisted of adolescents living with their parents, and 1104 adolescents were involved in the analysis. A multivariate logistic regression model of potentially contributing factors was employed to analyze the role of parental depression in adolescent depression. Results: A substantial portion of adolescents (21.2%) reported experiencing depression, with a higher prevalence observed among girls (25.3%). Adolescents were more likely to experience depression if their parents also reported depressive symptoms. According to 2014 data, as many as 25.4% of adolescents with mothers experiencing depression also reported feeling depressed. Meanwhile, 28.1% of adolescents experienced depression at the same time that their fathers felt depressed. Parental depression affected adolescent depression and had a significant and greater effect on female adolescents. Conclusion: This study revealed a strong association between parental depression and adolescent depression in Indonesia. The results underscore the importance of family-based interventions to reduce the adverse effects of depression on adolescents.